Analisis Pengaruh Utang Luar Negeri, Nilai Ekspor dan Kurs Terhadap Cadangan Devisa Negara Tahun 2014-2024 dalam Perspektif Ekonomi Islam - Muhammad Reza Falevi; Anas Malik; Taufiqurrahman Taufiqurrahman (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to examine the effect of foreign debt, export value, and exchange rates on foreign exchange reserves. The data used in this study is secondary data covering a 10-year period from 2014 to 2024. The analysis method used in this study is multiple regression. The software used to analyze the data in this study is Eviews 8. The results of the study indicate that foreign debt has a significant positive effect on foreign exchange reserves, export value has a non- significant positive effect on foreign exchange reserves, exchange rates have a non-significant positive effect on foreign exchange reserves, and foreign debt, export value, and exchange rates collectively affect a country's foreign exchange reserves from 2014 to 2024.